BUSINESS ANALYSIS DRIFT GILL NETS MOORING FISHING VESSEL IN PORT NUSANTARA SIBOLGA TAPANULI CENTRAL NORTH SUMATRA - Dicki Benediktus Ambarita; Lamun Bathara; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was conducted on 24 March to 9 April 2015 in the archipelago Fishing Port in Sibolga Central Tapanuli, North Sumatra Province. The method used is survey method, to determine the respondents conducted by purposive sampling that each one ship drift gill net GT size 20 and size 6 GT. Results from this study indicate that the investment amount of drift gill net vessels 20 GT is higher than the ship drift gill net 6 GT. While based on investment criteria using the feasibility analysis NPV, BCR and IRR, drift gill net vessels 20 GT and 6 GT is equally eligible to be forwardedFishing effort with drift gill nets were mooring the ship in the port of Sibolga Nusantara Fishery Central Tapanuli North Sumatra using several investment criteria still feasible to be developed. Fleet drift gill net with a size of 202GT NPV Rp. 1433472840, BCR of 1.91 and an IRR of 68.33%. Fleet drift gill net with size 6 GT NPV Rp. 759 909 400, BCR of 1.61 and an IRR of 67.4%.Keywords : NPV, BCR, IRR, Fleet, Drift Gill Net